Furthering scientific inquiry for weight loss maintenance: assessing the psychological processes impacted by a low intensity technology-assisted intervention (NULevel Trial) - Joyal-Desmarais, Keven; Rothman, Alexander J; Evans, Elizabeth H; Araújo-Soares, Vera; Sniehotta, Falko F. (Annals of behavioral medicine, 2024)
NULevel was a randomized control trial to evaluate a technology-assisted weight loss maintenance (WLM) program in the UK. The program included: (a) a face-to-face goal-setting session; (b) an internet platform, a pedometer, and wirelessly connected scales to monitor and report diet, physical activity, and weight, and; (c) regular automated feedback delivered by mobile phone, tailored to participants’ progress. Components were designed to target psychological processes linked to weight-related behavior. Though intervention participants showed increased physical activity, there was no difference in WLM between the intervention and control groups after 12 months (Sniehotta FF, Evans EH, Sainsbury K, et al. Behavioural intervention for weight loss maintenance versus standard weight advice in adults with obesity: A randomized controlled trial in the UK (NULevel Trial). PLoS Med. 2019; 16(5):e1002793. doi:10.1371/journal.pmed.1002793). It is unclear whether the program failed to alter targeted psychological processes, or whether changes in these processes failed to influence WLM.We evaluate whether the program influenced 16 prespecified psychological processes (e.g., self-efficacy and automaticity toward diet and physical activity), and whether these processes (at 6 months) were associated with successful WLM (at 12 months).288 adults who had previously lost weight were randomized to the intervention or control groups. The control group received wireless scales and standard advice via newsletters. Assessments occurred in person at 0, 6, and 12 months.The intervention significantly altered 10 of the 16 psychological processes, compared with the control group. However, few processes were associated with WLM, leading to no significant indirect effects of the intervention via the processes on WLM.Changes in targeted processes were insufficient to support WLM. Future efforts may more closely examine the sequence of effects between processes, behavior, and WLM.Many tools exist to help people lose weight, but it is common for people to regain that weight over time. Thus, understanding how to support the maintenance of weight loss remains a priority. The NULevel program was a 12-month weight loss maintenance (WLM) intervention for individuals who had recently lost weight. It promoted psychological factors, shown to be tied to weight-related behaviors, using face-to-face and technology-based (e.g., mobile phone feedback) elements. For example, the program encouraged making plans to improve lifestyles (e.g., exercise, better diet) and promoted people’s confidence in these behaviors. However, the program was not more successful than a control condition in maintaining weight loss. We sought to understand why this occurred. We found that the program was indeed successful in influencing most of the psychological factors it targeted. Instead, it was the psychological factors that failed to predict WLM. Were the psychological factors insufficient to impact behavior? Or did the promoted behaviors fail to aid WLM? Future research should focus on answering such questions. Doing so would inform whether interventions should target different psychological factors to change behaviors, or choose different sets of behaviors to support WLM.